Recurrent pleomorphic adenoma of minor salivary glands: A clinical analysis - XU Wanlin; LU Hao; WU Yifan; LIU Shengwen; YANG Wenjun (Kouqiang hemian waike zazhi)
[Objective:] To investigate the clinicopathological features and prognosis of recurrent pleomorphic adenoma (RPA) of minor salivary glands. [Methods:] The clinical data of patients with RPA of minor salivary glands in our hospital from January 2011 to December 2020 were retrospectively collected. In combination with literature review, the clinicopathological characteristics and prognosis were analyzed. [Results:] A total of 17 cases of RPA of minor salivary glands were collected, including 5 males and 12 females. The age ranged from 14 to 80 years, with a median age of 52 years. The average recurrence frequency was 2.8 times, and the average recurrence interval was 7.9 years. It was most common in the palate (52.9%), followed by the buccal (29.4%). Large recurrent tumors may cause certain symptoms, such as bone absorption, pharyngeal cavity obstruction and facial swelling. A total of 7 (41.2%) of 17 patients underwent malignant transformation, and 5 (55.6%) of 9 cases in the palate underwent malignant transformation. The prognosis of surgical treatment was good, with an average follow-up of 5.7 years, and 15 patients (88.2%) were tumor-free status. [Conclusion:] RPA of minor salivary glands is a rare critical tumor, which often occurs in the palate and has a long recurrence interval. RPA of small salivary gland is prone to undergo malignant transformation, and the prognosis of surgical treatment is good.